Wychowanie bez Boga – rugowanie religii z polskich szkół (1949-1956) - Jaworska, Kazimiera (Społeczeństwo, 2024)
The socio-political changes that occurred in Poland after World War II had a significant impact on the functioning of the education system at all levels, the reconstruction of which after the dramatic years of war and occupation was a priority. Schools and the associated possibilities for education provided a crucial tool for the new authorities to promote the new ideology. The consequence of the change from the pre-war educational ideal, which was state, national, and religious, to a secular one, was disturbances in the teaching of religion within school walls. Attempts to eliminate religious lessons from schools had a serious impact on the relationship between the Church and the state. During the so-called People’s Poland era, this issue was treated instrumentally by the ruling party, depending on the needs of the current government. Due to the pervasive indoctrination of communist ideology in Polish schools from 1949 to 1956, the subject of “religion” was almost completely eradicated from the school environment, even though it still appeared in the compulsory subjects catalog. The aim of this publication is to explore the issue of removing religious lessons from Polish schools between 1949 and 1956 based on available source documentation and scientific literature.